2001
DOI: 10.1007/s11771-001-0030-7
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility evaluation in vitro. Part II: Functional expression of human and animal osteoblasts on the biomaterials

Abstract: DNA synthesis and collagen formations on the implant material by cell culture in vitro are the most important phenotypical expression to estimate the biocompatibility. In this part, DNA synthesis and collagen formation on implant materials were quantitatively and qualitatively estimated by radioactive isotope H ÷ -thymidine to incorporate ir.to DNA chains, H + -proline to incorporate into type I collagen proteins followed by scintillation counting and antibody-antigen immunoeytochemistry staining, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As illustrated in figures 4(b)-(d), after incorporating BG powder into β-TCP powder, the pore size of composite materials became larger than that of pure β-TCP material. However, while increasing the BG powder to 4 wt%, the pore size of composite materials decreased slightly (figure 4e), revealing the crystallization of amorphous BG powder in composites during sintering at 1000 • C. As for the bioceramic materials, the pore size is a key factor for cell growth in pores and on the surface due to convenient entrance of sufficient nutrients and oxygen and metabolism (Fauter et al 2001;Ruan and Grant 2001). It has been demonstrated that open pores with pore size ranging from 100 to 800 μm favours body fluid invasion, cell colonization, vascularization and bone tissue ingrowth.…”
Section: Morphologymentioning
confidence: 99%
“…As illustrated in figures 4(b)-(d), after incorporating BG powder into β-TCP powder, the pore size of composite materials became larger than that of pure β-TCP material. However, while increasing the BG powder to 4 wt%, the pore size of composite materials decreased slightly (figure 4e), revealing the crystallization of amorphous BG powder in composites during sintering at 1000 • C. As for the bioceramic materials, the pore size is a key factor for cell growth in pores and on the surface due to convenient entrance of sufficient nutrients and oxygen and metabolism (Fauter et al 2001;Ruan and Grant 2001). It has been demonstrated that open pores with pore size ranging from 100 to 800 μm favours body fluid invasion, cell colonization, vascularization and bone tissue ingrowth.…”
Section: Morphologymentioning
confidence: 99%
“…While these reported studies have revealed possible concerns with the cellular response to metallic biomaterials, the ions they release are also a concern: such as alterations in enzyme activities; ATP levels, and DNA, RNA, and protein synthesis. Glutathione is involved in many biological functions and is widely distributed among living cells [4,5]. Electrophilic species released from materials may conjugate with GSH spontaneously, or more commonly, enzymatically through glutathione-S-transfer-ase.…”
Section: Introductionmentioning
confidence: 99%